Life and counselling experiences of elderly Malay residents in Rumah Seri Kenangan, Cheras, Malaysia - Rahimi, Mohd Khairul Anuar (2012)
This study is aimed at exploring the life and counselling experiences of elderly Malay residents in Rumah Seri Kenangan Cheras, Selangor by using reminiscence therapy and to gain insight about the meaning of those experiences to the residents. Life expectancy rates in Malaysia continue to grow, however the additional years are usually spent in negative state, with the elderly in frailty and riddled with disability in Long-term Care (LTC) Homes. Therefore, counselling becomes one of the factors which could help the elderly to live the remaining years of their life in a positive manner, thus helping them to achieve successful ageing. The study has two research questions: (1) What are the life experiences of residents in Rumah Seri Kenangan Cheras, and (2) What are the counselling experiences of the residents in Rumah Seri Kenangan Cheras This study employs a basic qualitative research design. Six elderly Malay residents were first provided counselling by the researcher using reminiscence therapy approach in a six-week individual counselling session. After the sessions ended, the respondents were interviewed for their feedback on the experiences that were gained through counselling. Both the counselling sessions and follow-up in-depth interview were recorded and transcribed verbatim. The data is then translated from Malay into English and were analysed by using the constant comparative method. The findings yielded twenty two themes based on the analyses of the themes. These themes were organized according to the research questions regarding their life andNcounselling experiences. The findings indicate nine emergent themes regarding their life experiences in the old folks’ home, including: (1) Sadness of Being Away From Close Relatives, (2) Using Humour in Everyday Life, (3) Concern About Death, (4) Loss of Independence, (5) Religion (Islam) as an Important Component of Everyday Life, (6) Reminiscence of Past Events, (7) Concern of their Health, (8) Not Getting Good,Balanced Diet, and (9) Advice-giving Role and Wisdom. From the emergent themes for the residents’ counselling experiences, there are thirteen themes: (1) Negative Initial Perception of Counselling, (2) Changing Perception of Counselling, (3) Coping With Fear/Anger Living in an Old Folks’ Home, (4) Talking as a Form of Therapy, (5) Increased Acceptance of One’s Self, (6) Increased Acceptance of The Effects of Ageing, (7) Importance of Continuing Involvement in Life, (8) Feeling Happier After Counselling Ends, (9) Acceptance of Counselling Services, (10) Pride in Previous Accomplishments, (11) Personal Empowerment, (12) Cherishing Past Memories, and (13) Introspection of Past Events. The findings showed the reminiscence therapy approach used for counselling has helped giving meaningful life and counselling experiences to the participants. The approach has allowed the respondents to look back at their past life to have a more positive outlook of their past. Therefore, counselling through reminiscence therapy in Long-term Care (LTC) institutions could be the best way to help the residents achieve successful ageing. It is hoped that further research could be done on counselling the elderly by using other therapeutic approaches and on other ethnic group.